The Effectiveness of Cooperative Integrated Reading and Composition Model in the Teaching and Learning Narrative Essay Writing - Wahyu Ningsih; Nur Khadijah Razak (Universitas Sembilanbelas November Kolaka, 2017)
activity is the most essential activity in human life. This is true, because communicating is not just about delivering and receiving information, but also expression, asking for responses and responding with all the complexities of language that are not always realized by everyone. Bahasa Indonesia as a means to think logically, analytically, creatively, and systematically makes one can easily make new innovations in everyday life especially in education. The 1945 Constitution explains Indonesia's position as a language of unity is very strong. Article 36 reads,